Arsenic concentration in hair as an indicator of exposure - A.K, Sharma; S, Sarmani; J.C, Tjell, (Malaysian Journal of Science, 2004)
Elevated concentrations of the extremely toxic arsenic in ground water occur in many parts of the world with largest population being exposed in the entire Bengal delta. Exposure to arsenic can occur through food, water, and air. One of the biological indicators of exposure to arsenic is its accumulation in hair. The arsenic concentrations in hair in this study indicate that the exposure decreased in the following order: West Bengal (India) > Thailand > Malaysia (Kuala Lumpur) > Denmark > Malaysia (Rural); however only in India, Thailand and Kuala Lumpur there is an indication of chronic arsenic exposure.